PERAN KOMPETENSI DALAM MENINGKATKAN KINERJA PEGAWAI BAGIAN SOSIAL SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Firman Wahyudi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this article is to analyse about the competency’s role in order to enhance employee performance at Social Department of East Kutai. The result shows that employee performance did not too optimal, but they are still produce good work achievement. The lack of performance quality is caused by less compentency.